Practicum students’ educational competencies of the postgraduate professional diploma program in teaching - Al Omery, Moath Khalaf; Hazaymeh, Wafa’ A; Altakhaineh, Abdel Rahman Mitib; Faqeeh, Mohammad Hussein; Al Aqtash, Salem Khalil; Musleh, Omran Ahmad; Mostafa, Imad Ibraheem (Research Journal in Advanced Humanities, 2026)
The study aimed to investigate the extent to which practicum students in the Postgraduate Professional Diploma Program in Teaching are practicing educational competencies. The sample consisted of 275 students who were randomly selected. The study sought to assess the current level of competency among these students in various domains of teaching, including planning for teaching, teaching skills, personal characteristics and classroom management, and evaluation. A questionnaire consisted of 50 items distributed over four domains of teaching: planning for teaching, teaching skills, personal characteristics and classroom management, and evaluation. The collected data were statistically analyzed through SPSS. The study results showed that the average scores for all domains combined were high, with the highest average score in the planning for teaching domain and the lowest average score in the evaluation domain. It also indicated that there were no significant differences in responses between respondents based on specialization or in the field. However, the study did find significant differences based on the cumulative average variable, with students who received an excellent rating having higher scores than those who received a good or very good rating. Overall, the study provides valuable insights into the level of educational competencies among practicum students.